Project-Based Learning: Chemistry Students’ Role in Fostering the Society in Recycling the Waste Cooking Oil - Imam Sahroni; Lutfia Isna Ardhayanti; Chancard Basumerda; Muhammad Miqdam Musawwa; Randy Ramadani (Universitas Islam Indonesia, 2022)
Project-based learning has been used globally as one of the effective methods to evaluate student performance in achieving the learning outcome of the chemistry subject. It became one of the priorities in implementing the new policy, Merdeka Belajar-Kampus Merdeka (MB-KM) from The Ministry of Education, Culture, Research and Technology in Indonesia. The student at the university level can join a project-based learning program conducted outside the classroom and supervised by the Project supervisor. We proposed the project-based learning program to maximize the chemistry students’ role in solving the waste cooking oil in society. The purpose of this program was to introduce the chemistry student to the real problem in the society and allow the dissemination of their innovative idea. The information prevailed from observing the activity, interviewing the students, and evaluating the student's performance. This project-based learning presented that students accomplish the information and knowledge they gain from the classroom into actions to solve the real problem in society. Keywords: project-based learning, Merdeka Belajar-Kampus Merdeka (MB-KM), waste cooking oil, chemistry students’ role